2007
DOI: 10.1007/s12110-007-9003-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the Friendship Preferences and Social Styles of Men and Women

Abstract: Several hypotheses on the form and function of sex differences in social behaviors were tested. The results suggest that friendship preferences in both sexes can be understood in terms of perceived reciprocity potential-capacity and willingness to engage in a mutually beneficial relationship. Divergent social styles may in turn reflect trade-offs between behaviors selected to maintain large, functional coalitions in men and intimate, secure relationships in women. The findings are interpreted from a broad soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
216
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(231 citation statements)
references
References 60 publications
6
216
0
9
Order By: Relevance
“…Machiavellianism was associated with lower scores on all of the six friendshipfunctions subscales. Although same-sex friendships are often labelled as being highly important to women and provide a variety of functions and resources (Jonason & Schmitt, 2012;Silverman & Choi, 2005;Vigil, 2007), women with higher levels of Machiavellianism may view such functions as unnecessary. It is not surprising that women with higher levels of Machiavellianism have reported that their friend provides them with less companionship, help, intimacy, reliable alliance, self-validation, and emotional security.…”
Section: Study 1 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machiavellianism was associated with lower scores on all of the six friendshipfunctions subscales. Although same-sex friendships are often labelled as being highly important to women and provide a variety of functions and resources (Jonason & Schmitt, 2012;Silverman & Choi, 2005;Vigil, 2007), women with higher levels of Machiavellianism may view such functions as unnecessary. It is not surprising that women with higher levels of Machiavellianism have reported that their friend provides them with less companionship, help, intimacy, reliable alliance, self-validation, and emotional security.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…Previous research has established that Machiavellianism is associated with emotional manipulation and managing the emotions of others in general (Austin et al, 2007;Austin & O'Donnell, 2013), but the current studies extended that research by focusing on the use of these strategies in a specific context of women's same-sex friendships. Machiavellianism in one party may support the use of emotional manipulation strategies (Ináncsi et al, 2015;Su et al, 2009;Vigil, 2007). Employing these strategies towards one person may be less risky for women higher on Machiavellianism than engaging in relational aggression, which requires the assistance of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurzban (2001) found that low level social signals such as mutual eye gaze, gentle touching, as well as instant virtual messages, increased cooperation relative to a control condition between men but not between women in a public goods game. The tendency of men, but not women, to cooperate more in response to simple social cues might reflect a difference in the forms and functions of intra-sexual coalitions (e.g., Hess & Hagen, 2006;Rucas et al, 2010;Vigil 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to family kinship and coworker relationships, friendship is unique in being voluntary and flexible and can be terminated by any party. Due to its personal rather than formal nature, friendship should be a good indicator for measuring social preferences, particularly social distances across different racial groups (Gonzalez et al, 2007;Huckfeldt, 1983;Kinzler et al, 2009;Verbrugge, 1977;Vigil, 2007;Zeng and Xie, 2008).…”
Section: Introductionmentioning
confidence: 99%